2009
DOI: 10.1002/cncy.20055
|View full text |Cite
|
Sign up to set email alerts
|

Current applications and future prospects of fine‐needle aspiration biopsy of locoregional lymph nodes in the management of breast cancer

Abstract: Staging of disease is routine in the evaluation of patients newly diagnosed with breast cancer. Assessment of palpable and/or nonpalpable locoregional lymph nodes is an important component of the initial staging.Ultrasound (US) is the favored imaging modality for the initial investigation of lymph nodes and results in a significant increase in the specificity of the overall evaluation when used in conjunction with fine-needle aspiration (FNA). This review provides a concise summary, based on published literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 63 publications
(59 reference statements)
1
25
1
1
Order By: Relevance
“…One to two passages were used per sample. The LN sample was immediately transferred to medium-10% (v/v) human AB serum (PAA, Pasching, Austria) in RPMI 1640 medium (Life Technologies, Paisley, U.K.)-by "washing" the FNA needle several times with the medium (19) and transported to the laboratory at ambient temperature. The number of white cells in the LN sample was counted in a hemocytometer after staining with trypan blue (1:3 dilution in PBS) and 4% (v/v) acetic acid to eliminate RBC contamination.…”
Section: Ultrasound-guided Ln Fna Biopsymentioning
confidence: 99%
See 1 more Smart Citation
“…One to two passages were used per sample. The LN sample was immediately transferred to medium-10% (v/v) human AB serum (PAA, Pasching, Austria) in RPMI 1640 medium (Life Technologies, Paisley, U.K.)-by "washing" the FNA needle several times with the medium (19) and transported to the laboratory at ambient temperature. The number of white cells in the LN sample was counted in a hemocytometer after staining with trypan blue (1:3 dilution in PBS) and 4% (v/v) acetic acid to eliminate RBC contamination.…”
Section: Ultrasound-guided Ln Fna Biopsymentioning
confidence: 99%
“…For this purpose, we have used minimally invasive ultrasoundguided fine-needle aspiration (FNA) of the LN, a technique commonly used in clinical practice for cancer diagnosis (19). Axillary LN aspiration was used to sample the draining LN following PPD administered intradermally in the forearm.…”
mentioning
confidence: 99%
“…Seven (6.5%) out of 108 FNAC specimens were insufficient for diagnosis. Immediate assessment of specimens by a pathologist might reduce the proportion of inadequate samples [45] and allow additional lymph node passes by the radiologist to improve quality [28]. For the 86 patients treated by primary surgery, the overall sensitivity was 72.55% and the specificity was 100% (Table 6) although identifiable non-suspicious nodes were punctured and aspirated for cytological pretreatment examination.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound (US) is a simple and well-accepted method to examine axillary and non-axillary lymph nodes associated with breast cancer. Recent publications have reported that routine axillary US combined with cytology or core biopsy is an effective method to evaluate lymph node metastases prior to surgery [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Thus, pretreatment axillary US for early breast cancer patients and needle sampling of morphologically abnormal lymph nodes are now widely recommended [36].…”
Section: Background and Objectivementioning
confidence: 99%
“…For almost a century, radical mastectomy plus axillary lymph node dissection, introduced by Halsted in 1882 until the 1970s of the 20th century (6), was the standard surgical treatment for all breast tumor stages, resulting in serious complications in the upper limb ipsilateral to surgery (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%